A clinical update on managed care implications for Australian psychiatric practice. (December 2021) - Looi, Jeffrey CL; Kisely, Stephen R; Bastiampillai, Tarun; Pring, William; Allison, Stephen
Objective: To provide a clinical update on private health insurance in Australia and outline developments in US-style managed care that are likely to affect psychiatric and other specialist healthcare. We explain aspects of the US health system, which has resulted in a powerful and profitable private health insurance sector, and one of the most expensive and inefficient health systems in the world, with limited patient choice in psychiatric treatment. Conclusions: Australian psychiatrists should be aware of changes to private health insurance that emphasise aspects of managed care such as selective contracting, cost-cutting or capitation of services. These approaches may limit access to private hospital care and diminish the autonomy of patients and practitioners in choosing the most appropriate treatment. Australian patients, carers and practitioners need to be informed about the potential impact of private managed care on patient-centred evidence-based treatment.